Tinjauan Literatur: Peran Literasi Keuangan dan Gaya Hidup dalam Penggunakan Layanan Paylater pada Generasi Z (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
The development of e-commerce and digital financial services has changed consumer behavior, particularly among Generation Z. One emerging innovation is the Paylater service, which offers convenience and flexibility in transactions. While providing easy access, the use of Paylater also has the potential to increase consumer behavior and impulsive purchases. This study aims to analyze the role of financial literacy and lifestyle in the use of Paylater services among Generation Z through the Systematic Literature Review (SLR) method. A total of ten scientific articles published in the last five years were analyzed to examine the relationship between financial literacy, lifestyle, and Paylater usage behavior. The results show that financial literacy has an inconsistent influence and tends to act as a controlling factor, while a consumptive and hedonistic lifestyle is the dominant factor driving Paylater use. In addition, behavioral factors such as impulsive purchases and technological convenience also strengthen the tendency to use these services. This study concludes that increasing financial literacy balanced with controlling a consumptive lifestyle is very influential in encouraging the wise and sustainable use of Paylater.